Supervision of the Quality of Refilled Drinking Water by the Health Office in Wolo District, Kolaka Regency - Maulid Maulid; Yulia Wahyu Ningsih; Anis Ribcalia Septiana (Jurnal Office, 2021)
The increasing demand for the availability of clean water has prompted some people to start a clean water supply business, especially in the supply of drinking water refill. In this regard, this research was conducted with the aim of analyzing the quality control of refilled drinking water by the Health Office in Wolo District, Kolaka Regency using qualitative research methods. Data collected through interviews, observation, and documentation. Informants were determined using the purposive sampling technique. The research data were analyzed using interactive model techniques. The results showed that the supervision carried out by the Kolaka District Health Office was not going well, so that refill drinking water businesses were still found that did not comply with the standards in accordance with the Minister of Health Regulation.